PENERAPAN KONSEP E-LEARNING DENGAN METODE GAMIFIKASI UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI PERGURUAN TINGGI - Feliks; Hendri (LPPM Universitas Dinamika Bangsa, 2021)
To meet the needs of digital transformation, Indonesia needs young people who are able to compete globally. The education industry has taken advantage of this trend by integrating new methods such as virtual collaboration, mobile learning applications and enhanced learning technologies. In this study, researchers tried to apply the concept of Elearning / distance learning using the gamification method so as to improve the quality of learning in higher education. Gamification method provides additional motivation to ensure students (learners) follow complete learning activities and the ability to solve problems.